Cuidados e educação na pandemia: Uma abordagem a partir dos feminismos latino-americanos / Care and education in the pandemic: An approach based on latin american feminisms - Bonavitta, Paola (2021)
Fil: Bonavitta, Paola. Universidad Nacional de Córdoba. Facultad de Filosofía y Humanidades. Centro de Investigaciones María Saleme Burnichón; Argentina.